Uncertainty and adaptation in the context of Brexit: An entrepreneurial action and dynamic capabilities approach - Duarte Alonso, Abel; Kok, S.; O'Brien, S. (2019)
Purpose: The purpose of this study is to propose a framework to understand firms’ adaptation to uncertainty and change, specifically, in regards to the perceived impacts of the Brexit phenomenon. In doing so, the study considers entrepreneurial action theory (EAT) and the dynamic capabilities approach (DCA). Design/methodology/approach: Face-to-face interviews were conducted with owners and managers of 34 family-run firms operating in Italy’s Prosecco Superiore and Spain’s Cava industries. Findings: The element of uncertainty because of the imminent Brexit decision clearly emerged and was demonstrated through various effects on firms including the falling British Pound. The findings revealed that combining the EAT and the DCA provides a stronger explanation in understanding adaptation to uncertainty. For example, sensing (DCA) was suggested to be a precursor of opportunity attention and evaluation (EAT) or recognising opportunities and was subsequently manifested by operators’ action or seizing (DCA), including through more involvement in exports and wine tourism. Originality/value: The study is one of the few efforts to date to examine the potential impacts of an uncontrollable contemporary phenomenon, and ways to adapt from the perspective of entrepreneurs involved in a traditional and socioeconomically significant industry. The different adaptive strategies that emerged from the findings can provide practical insights. The proposed framework emphasises the theoretical and practical value of understanding adaptation through the lens of the adopted theoretical foundations.